Analisis Fungsi Keluarga (Family Apgar) Terhadap Kualitas Hidup Penderita Kusta - Andri Catur Jatmiko; Sri Adila Nurainiwati; Zhenna Vinenzha Linda Drestania (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
Leprosy is an infectious disease that causes a great stigma in society. Stigma against leprosy in the community makes sufferers delay or avoid treatment until later disability and unproductive occur so that further affects the quality of life of sufferers.The family is the smallest unit of society that is closely related to supporting a person's quality of life. This study aims to analyze the effect of family function (Family APGAR) on the quality of life of leprosy patients in Tuban Regency. This researchmethod is an analytic observational study with the research design used is the cross sectional method and uses a simple random sampling cluster sampling technique. The sample in this study amounted to 142 people who were in all health centers of the TubanDistrict Health Office. Hypothesis test using Spearman correlation test and logistic regression test. Spearman correlation test obtained p-value (0.001 <0.05) and concluded that there is a significant relationship between family function and quality of life of leprosy patients. In the logistic regression test, the factors that significantly influence the quality of life of leprosy patients are resolve with p-value (0.021 <0.05) with a probability of 56.58%. Family function (Family APGAR) affects the quality of life of people with leprosy and the most influential factor is resolve.